Learning from combination HIV prevention programmes to face COVID-19 emerging pandemic (Colombia Medica, 2020)
Before a vaccine against SARS-CoV-2 became available, several measures to control COVID-19 pandemic are necessary. Analogously, in the absence of an available vaccine, Combination HIV Prevention Programmes have consolidated a large experience of biomedical, behavioral and structural interventions suitable for several epidemiological settings. Adaptation of such experiences can organize mid-term and long-term responses to face COVID-19